1999
DOI: 10.1175/1520-0434(1999)014<0851:sebotn>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy Balance of the NCEP MRF and NCEP–NCAR Reanalysis in Antarctic Latitudes during FROST*

Abstract: The surface energy budget in Antarctic latitudes is evaluated for the medium-range numerical weather forecasts produced by the National Centers for Environmental Prediction (NCEP) and for the NCEP-National Center for Atmospheric Research reanalysis project during the winter, spring, and summer special observing periods (SOPs) of the Antarctic First Regional Observing Study of Troposphere project. A significant change in the energy balance resulted from an extensive model update beginning with the forecasts ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
0
32
2
Order By: Relevance
“…SCAM contains the vertical radiation, cloud and surface-process physics of the NCAR Community Atmospheric Model but spans only a single lateral grid box, here made to coincide with the Dome F ice-core site. We specify a sensible heat-flux convergence of 100 W m −2 and a latent heat-flux convergence of 50 W m −2 , consistent with the annual average convergences over Antarctica found in the NCEP/NCAR reanalysis 43 (but which are uncertain 44 ). The latent and sensible heat convergences are distributed so as to generate uniform warming within the troposphere.…”
Section: Methodsmentioning
confidence: 77%
“…SCAM contains the vertical radiation, cloud and surface-process physics of the NCAR Community Atmospheric Model but spans only a single lateral grid box, here made to coincide with the Dome F ice-core site. We specify a sensible heat-flux convergence of 100 W m −2 and a latent heat-flux convergence of 50 W m −2 , consistent with the annual average convergences over Antarctica found in the NCEP/NCAR reanalysis 43 (but which are uncertain 44 ). The latent and sensible heat convergences are distributed so as to generate uniform warming within the troposphere.…”
Section: Methodsmentioning
confidence: 77%
“…Data collected at the South Pole are not only of climatological interest to the Antarctic community, but are also useful in evaluating the output of weather and climate forecast models as well as satellite retrievals of climate variables (e.g., Briegleb and Bromwich 1998;Hines et al 1999;Pavolonis and Key 2003;Guo et al 2003;Pavolonis et al 2004;Hines et al 2004). In addition, understanding the behavior of clouds and their properties is important for understanding Antarctic climate.…”
Section: ϫ3mentioning
confidence: 99%
“…Lubin et al (1998) found that changing the specified phase and particle size for Antarctic clouds in the National Center for Atmospheric Research (NCAR) Community Climate Model Version 2 (CCM2) caused significant changes in the atmospheric circulation of the Southern Hemisphere. Other studies have revealed that current cloud parameterizations limit the success of Antarctic climate and weather simulations (Hines et al 1999(Hines et al , 2004. The problems associated with these parameterizations are due in part to the lack of adequate ground-truth data.…”
Section: ϫ3mentioning
confidence: 99%
See 1 more Smart Citation
“…FCC has been identified as an important and poorly predicted parameter in forecasts of Antarctic climate (Hines et al 1999(Hines et al , 2004. It is important for closing the surface heat budget (Pavolonis and Key 2003), but recent efforts have been relatively unsuccessful at estimating the magnitude of any one component of the radiative surface heat budget, probably in large part because of poor knowledge of FCC.…”
Section: Introductionmentioning
confidence: 99%